Review of Appling Anaerobic Fluidized Bed Reactor (AFBR) in Domestic Sewage treatment (Eurasian Journal of Engineering and Technology, 2022)
The purpose of this review is to present a study on Anaerobic Fluidized Bed Reactor (AFBR) in Domestic sewage treatment and how to use this type of treatment in several applications. So it is a simple description of the fluidized reactor, phenomena of fluidization actions, and the advantage of using the biomass as a source of power